Kinetika Pembentukan Hidroksimetilfurfural (HMF) pada Madu MultifloralMurni dan Teradulterasi Selama Pemanasan - Ajeng Dyah Kurniawati; Evia Zunita Dwi Pratiwi; Fitranaya Arlian Cintaya Dewi; Giovanni Raharja (Jurnal Teknologi dan Mutu Pangan, 2026)
Heating can reduce honey quality by increasing hydroxymethylfurfural (HMF), while adulteration with liquid palm sugar has the potential to alter the chemical characteristics of honey and accelerate HMF formation. This study aims to compare the kinetics of HMF formation in pure multifloral honey and multifloral honey adulterated with liquid palm sugar during heating, as well as to determine the reaction rate constant and activation energy for HMF formation. The research was conducted experimentally by heating pure and adulterated multifloral honey at temperatures of 50, 60, 70, 80, and 90oC for 0–30 minutes with two replicates. HMF formation was analyzed using zero-order and first-order kinetic models, while the effect of temperature was analyzed using the Arrhenius model. The results showed that adulterated honey had higher initial HMF levels and greater increases in HMF (110.58–409.52%) compared to pure honey (25.88–199.31%). The activation energy for HMF formation was 40.34 kJ/mol in pure honey and 16.20 kJ/mol in adulterated honey. The conclusion of this study is that adulteration with liquid palm sugar can accelerate HMF formation during heating, so kinetic parameters have the potential to be used to optimize the honey processing process to improve the quality of the honey produced.